Optimal. Leaf size=31 \[ -e^{\frac {1}{3} \left (5-\log \left ((6-x) x^2\right )\right )}+3 x-x \log (20) \]
________________________________________________________________________________________
Rubi [A] time = 0.92, antiderivative size = 31, normalized size of antiderivative = 1.00, number of steps used = 4, number of rules used = 3, integrand size = 57, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.053, Rules used = {1593, 6742, 1588} \begin {gather*} x (3-\log (20))-\frac {e^{5/3}}{\sqrt [3]{6 x^2-x^3}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 1588
Rule 1593
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{\frac {1}{3} \left (5-\log \left (6 x^2-x^3\right )\right )} (-4+x)-18 x+3 x^2+\left (6 x-x^2\right ) \log (20)}{(-6+x) x} \, dx\\ &=\int \left (\frac {e^{5/3} (4-x) x}{\left (6 x^2-x^3\right )^{4/3}}+3 \left (1-\frac {\log (20)}{3}\right )\right ) \, dx\\ &=x (3-\log (20))+e^{5/3} \int \frac {(4-x) x}{\left (6 x^2-x^3\right )^{4/3}} \, dx\\ &=-\frac {e^{5/3}}{\sqrt [3]{6 x^2-x^3}}+x (3-\log (20))\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.18, size = 27, normalized size = 0.87 \begin {gather*} -\frac {e^{5/3}}{\sqrt [3]{-\left ((-6+x) x^2\right )}}-x (-3+\log (20)) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [B] time = 0.73, size = 52, normalized size = 1.68 \begin {gather*} \frac {3 \, x^{4} - 18 \, x^{3} - {\left (x^{4} - 6 \, x^{3}\right )} \log \left (20\right ) + {\left (-x^{3} + 6 \, x^{2}\right )}^{\frac {2}{3}} e^{\frac {5}{3}}}{x^{3} - 6 \, x^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.24, size = 27, normalized size = 0.87 \begin {gather*} -x {\left (\log \left (20\right ) - 3\right )} - e^{\left (-\frac {1}{3} \, \log \left (-x^{3} + 6 \, x^{2}\right ) + \frac {5}{3}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [F] time = 0.03, size = 0, normalized size = 0.00 \[\int \frac {\left (x -4\right ) {\mathrm e}^{-\frac {\ln \left (-x^{3}+6 x^{2}\right )}{3}+\frac {5}{3}}+\left (-x^{2}+6 x \right ) \ln \left (20\right )+3 x^{2}-18 x}{x^{2}-6 x}\, dx\]
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} -x {\left (\log \relax (5) + 2 \, \log \relax (2) - 3\right )} + \int \frac {x e^{\frac {5}{3}} - 4 \, e^{\frac {5}{3}}}{{\left (x^{\frac {8}{3}} - 6 \, x^{\frac {5}{3}}\right )} {\left (-x + 6\right )}^{\frac {1}{3}}}\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [F] time = 0.00, size = -1, normalized size = -0.03 \begin {gather*} -\int \frac {\ln \left (20\right )\,\left (6\,x-x^2\right )-18\,x+{\mathrm {e}}^{\frac {5}{3}-\frac {\ln \left (6\,x^2-x^3\right )}{3}}\,\left (x-4\right )+3\,x^2}{6\,x-x^2} \,d x \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} - \int \frac {4 e^{\frac {5}{3}}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\, dx - \int \frac {18 x \sqrt [3]{- x^{3} + 6 x^{2}}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\, dx - \int \left (- \frac {x e^{\frac {5}{3}}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\right )\, dx - \int \left (- \frac {3 x^{2} \sqrt [3]{- x^{3} + 6 x^{2}}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\right )\, dx - \int \left (- \frac {6 x \sqrt [3]{- x^{3} + 6 x^{2}} \log {\left (20 \right )}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\right )\, dx - \int \frac {x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} \log {\left (20 \right )}}{x^{2} \sqrt [3]{- x^{3} + 6 x^{2}} - 6 x \sqrt [3]{- x^{3} + 6 x^{2}}}\, dx \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________